Un puente hasta Therabithia - Paterson, Katherine (Madrid : Alfaguara, 1988)
The life of a boy in rural Virginia expands when he becomes friends with a newcomer who subsequently meets an untimely death. . .
5-8
5-8
L.A. Recommended Foreign Language
Keywords: Newbery medal books; Spanish language materials; Friendship -- Fiction; Death -- Fiction; Friendship -- Fiction; Death -- Fiction; Spanish language; Newbery Medal